Managing Conflicts in Schools: A Stakeholder’s Analysis for Students, Teachers and Administrators - Adeeba Khurshid (Research Journal of Psychology, 2024)
The purpose of this paper is to examine conflict management in schools. The paper will explore the nature of conflicts in schools, their origin and explanations proposed by the researches. In addition the researcher will investigate the implications of that the stakeholders involved; namely, the students, teachers and administrators. The researcher formulated the following hypotheses 1) Aggressive children particularly those who are rejected by the peer group, experience multiple difficulties in encoding and interpreting cues in social interactions.2) Training students in conflict management interventions facilitate a positive appraisal of conflicting situations, offering effective mediums for their resolution and convincing motivation for their applications.3) It is predicted that teachers high in self-reported classroom management efficacy (CMEFF) and security of attachment (low on avoidance, anxiety) will validate the use of positive classroom management strategies (e.g., integrating, compromising), resulting in positive conflict management in classes more than insecure teachers and those low in CMEFF. 4) Administrators‟ (leaders) behaviors that involve higher levels of emotional management will be strongly related to improved levels of job performance. 5) In addition, higher levels of inspiration and communication of vision by leaders will be directly associated with lower levels of intimidation by the staff members. The analysis revealed a strong relationship in all except the first hypothesis through the rigorous content examination.